2022
DOI: 10.1001/jamacardio.2021.4822
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Training Response for Women in Cardiac Rehabilitation

Abstract: eak aerobic exercise capacity, measured as peak oxygen uptake (peak VO 2 ), is a powerful predictor of mortality among cardiac patients. 1 Despite having lower fitness at baseline, women generally do not improve peak VO 2 as much as men in phase 2 cardiac rehabilitation (CR). 2,3 In a prior study of 1789 patients performing standard CR training, women improved by a mean (SD) 0.3 (0.4) L/min and men improved by a mean (SD) 0.4 (0.5) L/min (14% vs 19%, respectively). 3 High-intensity interval training (HIIT) has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
2
15
0
2
Order By: Relevance
“…Primary support given for this conclusion centered on the larger change in peak V o 2 for HIIT (n = 22) vs MCT (n = 21) participants (mean [SD] peak V o 2 : HIIT, 0.3 [0.2] L/min; MCT, 0.1 [0.2] L/min; P = .03). However, peak V o 2 changes were not significantly different between groups when analyzed in typical units of mean (SD) mL/kg/min, consistent with peak V o 2 increasing within both HIIT (entry, 18.8 [3.7] mL/kg/min; exit, 22.6 [4.7] mL/kg/min; P < .001) and MCT (entry, 19.3 [4.8] mL/kg/min; exit, 21.9 [5.9] mL/kg/min; P < .001) . This similarity is noteworthy given the powerful prognostic value associated with peak V o 2 in mL/kg/min, as noted in background evidence cited by the authors, which we also agree with .…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Primary support given for this conclusion centered on the larger change in peak V o 2 for HIIT (n = 22) vs MCT (n = 21) participants (mean [SD] peak V o 2 : HIIT, 0.3 [0.2] L/min; MCT, 0.1 [0.2] L/min; P = .03). However, peak V o 2 changes were not significantly different between groups when analyzed in typical units of mean (SD) mL/kg/min, consistent with peak V o 2 increasing within both HIIT (entry, 18.8 [3.7] mL/kg/min; exit, 22.6 [4.7] mL/kg/min; P < .001) and MCT (entry, 19.3 [4.8] mL/kg/min; exit, 21.9 [5.9] mL/kg/min; P < .001) . This similarity is noteworthy given the powerful prognostic value associated with peak V o 2 in mL/kg/min, as noted in background evidence cited by the authors, which we also agree with .…”
mentioning
confidence: 58%
“…To the Editor In a recent article by Khadanga et al, it is reported that among women participating in phase 2 cardiac rehabilitation, undergoing an exercise intervention involving high-intensity interval training (HIIT) and intensive lower extremity resistance training (RT) yields significantly larger increases in peak exercise oxygen uptake (peak V o 2 ) compared with changes resulting from moderate-intensity continuous training (MCT) and low-intensity RT. Primary support given for this conclusion centered on the larger change in peak V o 2 for HIIT (n = 22) vs MCT (n = 21) participants (mean [SD] peak V o 2 : HIIT, 0.3 [0.2] L/min; MCT, 0.1 [0.2] L/min; P = .03).…”
mentioning
confidence: 99%
“…In Reply We appreciate the thoughtful commentary from Terada et al and Van Iterson et al to our article . In our study, the moderate continuous training (MCT) group achieved a modest yet significant weight loss, while the high-intensity interval training (HIIT) group remained weight stable.…”
mentioning
confidence: 68%
“…In addition to ET being a low-cost approach, its effectiveness for disease prevention 11 and treatment 12,13 is well established in the literature. According to Ruberti et al, moderate-intensity aerobic ET is capable of promoting reduction of cardiometabolic alterations in cardiac tissue, reduction of collagen fraction after infarction and maintaining lower blood pressure levels compared to the sedentary group, although this difference is not statistically significant 14 .…”
mentioning
confidence: 99%